Influence of Social Pressures on the Academic Performance of HUMSS Students at NU-Nazareth - Garcia, Ghian Louie; Moral, Marinell; Rocete, Angeline Rose; Ilagan, Marithe; Cabido, John Claude; Escueta, Hannah Gabrielle; Novilla, Ken Joseph; Retone, Lourence (Edukasiana: Jurnal Inovasi Pendidikan, 2024)
This study aims to investigate the influence of social pressures on the academic performance of Humanities and Social Sciences (HUMSS) students at NU-Nazareth. Students may experience various types of social pressure, including peer pressure, family pressure, and academic pressure, which can impact their academic performance and well-being. Social pressure is the influence exerted on an individual by peers, family, or society to conform to certain behaviors, leading to affect their motivation, focus, and overall success in school. Insufficient literature on social pressures experienced by HUMSS students, their impact on academic performance, and coping mechanisms are the reasons why the researchers conducted this study. The study will be utilizing qualitative research employing a phenomenological approach to identify how external factors affect a student's academic success, explore the different ways in which social pressures impact academic performance, and know the coping mechanism that HUMSS students use to manage social pressure in order to achieve their academic goals. Using thematic analysis, the findings of the study were: 1.) HUMSS Students Experienced Family Pressure as the Most Common Type of Social Pressure Driven by High Standards and Expectations by Parents; 2.) The Influence of Social Pressure to the Academic Performance of HUMSS Students; 3.) HUMSS Students' Strategies for Managing and Coping with Social Pressures. Based on the study's findings, it is crucial for parents to engage in open communication with their children, balancing aspirations with realistic expectations, and encouraging dialogue about academic goals and challenges. Moreover, future research should delve into the potential long-term effects of social pressure on students' academic, physical, and personal well-being beyond their time in educational institutions, employing both qualitative and quantitative approaches for a comprehensive understanding in sociology and psychology.